Lipoic acid significantly restores, in rats, the age-related decline in vasomotion - Smith, A R (Nature Publishing Group, 2008)
Background and purpose: The age-related decline in vasorelaxation is largely due to ceramide-induced induction of phosphatase 2A (PP2A), which limits nitric oxide synthase (eNOS) phosphorylation at stimulatory sites. We hypothesized that ceramide accumulation was from an age-related loss of endothelial glutathione (GSH) and subsequent activation of neutral sphingomyelinase (nSMase), an enzyme whose activity increases when GSH is limited. Experimental approach: Old (30-32 mo) F344xBN rats were given (R)-α-lipoic acid (LA), an agent known to induce GSH synthesis. Vasorelaxation was measured in aortic rings; GSH and ceramide levels, activity of nSMase and eNOS phosphorylation (by Western blot) was measured in aortic endothelial cells, isolated from the same aortas. Key results: In old animals, endothelium-dependent relaxation in aortic rings was decreased, GSH levels and its redox state in aortic endothelia were over 30% lower and nSMase activity and endothelial ceramide levels were three-fold increased, relative to young (2-4 mo) rats. LA treatment of old animals improved relaxation in aortic rings, reversed the changes in endothelial GSH, in nSMase activities and in ceramide levels. Similar effects on GSH levels and nSMase activity in old rats were also induced by treatment with GSH monoethylester. Activation (by phosphorylation) of eNOS was decreased by about 50% in old rats and this age-related decrease was partially reversed by LA treatment. Conclusions and implications: Decreased endothelial GSH was partly responsible for the age-related loss of vascular endothelial function and LA might be therapeutically evaluated to treat endothelial dysfunction.